2015
DOI: 10.1021/acs.jced.5b00310
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Halogenated Hydrocarbons in Hydrophobic Ionic Liquids: Experimental Study and COSMO-RS Prediction

Abstract: Halogenated hydrocarbons are members of priority water contaminants because of their negative health and environmental impacts. In this study, the solubility of three halogenated hydrocarbons, namely, carbon tetrachloride, chloroform, and bromoform was measured in 12 hydrophobic ionic liquids (ILs) for temperature ranging between 25 and 45 °C. We investigated the chemical structure and alkyl chain length effect of three different cations (piperidinium, pyrrolidinium, and ammonium-based) paired with bis­(triflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…20 It has also attracted a significant amount of attention in terms of ILs, as it integrates the dominant interaction forces of H-bonds, misfits and van der Waals in ILs systems. [21][22] Many results on the prediction of polymer properties in ILs have been reported, and it is obvious that calculating the activity coefficients, 23 solubility coefficients 1,24 and excess enthalpy 25 of polymer in ILs is an effective way of evaluating the dissolution ability of the ILs. Casas et al, 26 for instance, found that the solubility of cellulose and lignin could be accurately predicted by using activity coefficients and excess enthalpy via COSMO-RS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 It has also attracted a significant amount of attention in terms of ILs, as it integrates the dominant interaction forces of H-bonds, misfits and van der Waals in ILs systems. [21][22] Many results on the prediction of polymer properties in ILs have been reported, and it is obvious that calculating the activity coefficients, 23 solubility coefficients 1,24 and excess enthalpy 25 of polymer in ILs is an effective way of evaluating the dissolution ability of the ILs. Casas et al, 26 for instance, found that the solubility of cellulose and lignin could be accurately predicted by using activity coefficients and excess enthalpy via COSMO-RS.…”
Section: Introductionmentioning
confidence: 99%
“…COSMO-RS, a well-defined method for predicting the thermophysical properties of liquids, is a useful tool for predicting the solubility of polymers through the hypothesis that polymers can be treated as solutions consisting of monomers or oligomers with a small number of repeat units . It has also attracted a significant amount of attention in terms of ILs, as it integrates the dominant interaction forces of H bonds, misfits, and van der Waals in ILs systems. , Many results on the prediction of polymer properties in ILs have been reported, and it is obvious that calculating the activity coefficients, solubility coefficients, , and excess enthalpy of polymer in ILs is an effective way of evaluating the dissolution ability of the ILs. Casas et al, for instance, found that the solubility of cellulose and lignin could be accurately predicted by using activity coefficients and excess enthalpy via COSMO-RS.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction errors can probably be attributed to the weak interactions in p -MeSt–IL systems; however, this does not affect the predicted trend. COSMO-RS is thus a suitable tool for ranking ILs qualitatively in terms of the solubilities of vinyl monomers in ILs …”
Section: Results and Discussionmentioning
confidence: 99%
“…COSMO-RS is thus a suitable tool for ranking ILs qualitatively in terms of the solubilities of vinyl monomers in ILs. 38 3.2. Solubilities of p-MeSt and IBVE in ILs.…”
Section: Resultsmentioning
confidence: 99%
“…The nitrogen analyzer was used to measure the solubilities of five typical ILs in the examined hydrocarbons, revealing COSMO-RS's adequate capacity to forecast IL-in-hydrocarbon solubilities. AlSaleem 16 investigated the solubility of three halogenated hydrocarbons in 12 hydrophobic ILs at temperatures ranging from 25 to 45 °C. Piperidinium, pyrrolidinium, and ammonium-based cations coupled with [TF 2 N] anion were studied for their chemical structure and alkyl chain length impact.…”
Section: Introductionmentioning
confidence: 99%